The Effect of Stress Levels on Employee Job Performance at Hospital X - Sutanti, Yosephin S; Handoko, Yusuf; Techrisna, Erdy; Winata, Susanty D.; Marni, Maria (Dinasti International Journal of Management Science, 2026)
Stress is a physical and emotional response that occurs due to demands that are inconsistent with an individual's abilities. Job performance is the result of an employee's work over a certain period compared to predetermined standards, targets, or criteria. Continuously increasing stress to an optimal level tends to improve employee job performance. This study aims to determine the effect of stress levels on employee job performance at Hospital X. This study used a cross-sectional design in June 2022. Respondents were employees at Hospital X, taking data from the entire population. Stress was measured using the Perceived Stress Scale (PSS 10) questionnaire, and job performance using the Manurung Job Performance Questionnaire. The results of the study showed that employees working at Hospital X were predominantly health workers, female, relatively young (≤40 years old) and had worked for more than or equal to one year. Furthermore, 121 employees experienced moderate stress, followed by 99 employees experiencing mild stress, and only one person experiencing severe stress. Most employees had good work performance, with 212 employees experiencing poor work performance, and only nine had poor work performance. The Fisher exact test found a significant relationship between stress levels and work performance among employees at Hospital X with a p-value of 0.044.